Marmota (Petromarmota) caligata Eschscholtz 1829 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Marmota (Petromarmota) caligata Eschscholtz 1829 Marmota (Petromarmota) caligata Eschscholtz 1829, Zool. Atlas, Part 2: 1. Type Locality: Not specified (?). Restricted by J. A. Allen (1877:927) to near Bristol Bay, Alaska, USA. Vernacular Names: Hoary Marmot. Subspecies:: Subspecies Marmota (Petromarmota) caligata subsp. caligata Eschscholtz 1829 Subspecies Marmota (Petromarmota) caligata subsp. cascadensis A. H. Howell 1914 Subspecies Marmota (Petromarmota) caligata subsp. okanagana King 1836 Distribution: C Alaska (USA), Yukon and Northwest Territories (Canada) south to W and NE Washington, C Idaho, and W Montana (USA). Conservation: IUCN – Data Deficient as M. c. sheldoni and M. c. vigilis otherwise – Lower Risk (lc). Discussion: Subgenus Petromarmota (Steppan et al., 1999). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Sciuridae, pp. 754-818 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 800, DOI: 10.5281/zenodo.7316535